2016
DOI: 10.1625/jcam.13.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intake of Astaxanthin Contained Drink on Skin Condition

Abstract: Objectives: To study the effect of astaxanthin contained drink to skin condition Methods: The study was conducted to the Japanese females between age over thirty to less than fifty, who had weakening of skin (including aging, sag and dry skin) and skin dullness. In order to conduct the objective evaluation, the comparison between the groups by the double-blind test was taken. Twenty of subjects were randomly allocated to the intake group of astaxanthin contained drink (astaxanthin 3mg contained) and the placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Several clinical trials showed that astaxanthin on the dermal layer contributed to the improvement of wrinkles. ,− This indicates that astaxanthin serves to maintain the extracellular matrix (ECM) of the dermis layer. In particular, it is believed that astaxanthin quenches singlet molecular oxygen, , which is involved in the damage of collagen-based ECM-producing fibroblasts, and also inhibits enzymatic activities and/or suppresses the gene expression of MMPs, which are involved in the degradation of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials showed that astaxanthin on the dermal layer contributed to the improvement of wrinkles. ,− This indicates that astaxanthin serves to maintain the extracellular matrix (ECM) of the dermis layer. In particular, it is believed that astaxanthin quenches singlet molecular oxygen, , which is involved in the damage of collagen-based ECM-producing fibroblasts, and also inhibits enzymatic activities and/or suppresses the gene expression of MMPs, which are involved in the degradation of ECM.…”
Section: Discussionmentioning
confidence: 99%